Is the perceived public stigma of smokers associated with value opposites? An exploratory cross-sectional analysis of Norwegian data 2011–2013 - Sæbø, Gunnar; Lund, Marianne (Frontiers in Sociology, 2024)
Smoker stigma is a likely unintended consequence of tobacco polices aiming to denormalise smoking. Little is known about the dissemination of stigmatising attitudes toward smokers at the population level, including their associations with personal values. Applying a theoretical approach that conceptualises stigma as a cultural (moral and intersubjective) issue, we analyse the spread of perceived public stigma of smokers in Norway and factors predicting agreement with such a perception. Using merged data from the biennial national survey Norwegian Monitor 2011 and 2013 (N = 7,792), we tested whether the tendency to agree with a perceived public stigma of smokers differs by four indexes of value opposites (‘puritanism/emancipation,’ ‘conformity/individuality,’ ‘tolerance/intolerance,’ ‘status/anti-status’), controlling for smoking status, SES, and demographics. Descriptive statistics and block-wise logistic regression models were applied. In the total sample, 59.1% agree with the statement that ‘most people think less of a person who smokes.’ Two of the four indexes of value opposites tested were associated with tendencies to agree with the perceived public stigma of smokers (‘puritanism/emancipation’ and ‘status/anti-status’). Smokers with current plans to quit expressed the highest perceived public stigma, while ex-smokers expressed a higher perceived public stigma than never-smokers. Women, young people and respondents with high SES agree with a public stigma of smokers more than men, older people and respondents with low SES do. The perceived public stigma of smokers is high in Norway and varies to some extent with personal values, but also with socio-demographics and especially smoking status.